The Impact of Oil Prices on the Banking System in the GCC - Khandelwal, Padamja (IMF Working Papers; Working Paper ;, 2016)
This paper examines the links between global oil price movements and macroeconomic and financial developments in the GCC. Using a range of multivariate panel approaches, including a panel vector autoregression approach, it finds strong empirical evidence of feedback loops between oil price movements, bank balance sheets, and asset prices. Empirical evidence also suggests that bank capital and provisioning have behaved countercyclically through the cycle.